A deixis emocional em português europeu contemporâneo: alguns contributos - Macário Lopes, Ana Cristina (Revista da Associação Portuguesa de Linguística, 2019)
This paper is a contribution to the description of the structures that express emotional deixis, in European contemporary Portuguese. The analysis of our empirical data show that, in Portuguese, demonstratives are not the only category that encodes emotional deictic meaning; possessives and first person plural display the same function, in some contexts. It is also discussed the semantic bleaching of the deictic space adverbs cá and lá and it is argued that it can only be described and explained in illocutionary terms, and not in the framework of emotional deixis.